Knowledge, Attitudes and Practices Towards Psoriasis Among Patients and Their Family Members - Zhang X; Du H; Liu X; Liu L; Zhang T (Dove Medical Press, 2024)
Xiaolan Zhang, Hongyang Du, Xiaoxiao Liu, Luyao Liu, Tingwei Zhang Department of Dermatology, The First Affiliated Hospital of JinZhou Medical University, Jinzhou, 121001, People's Republic of ChinaCorrespondence: Xiaolan Zhang, Department of Dermatology, The First Affiliated Hospital of JinZhou Medical University, Jinzhou, 121001, People's Republic of China, Tel +86-13840698157, Email xiaolanzhang_84@163.comPurpose: KAP studies serve to enhance health consciousness and furnish foundational data for appraising, strategizing, and enacting disease management and prejudice eradication initiatives. There remains a dearth of published studies elucidating the dimensions of knowledge, attitudes, and practices among psoriasis patients in China. To investigate the knowledge, attitudes and practices (KAP) towards psoriasis among patients and their family members in Northern China.Methods: This web-based, cross-sectional study was conducted among psoriasis patients and their family members through a self-administered questionnaire.Results: Among patients (n=260), their mean KAP scores were 9.76± 5.69 (range: 0- 19), 35.64± 11.48 (range: 14- 70), and 56.73± 10.98 (range: 16- 80), respectively. Among family members (n=237), their mean KAP scores were 11.93± 5.34 (range: 0- 19), 35.80± 4.34 (range: 8- 40), and 37.04± 4.38 (range: 8- 40), respectively. Structural equation modeling (SEM) analysis for patients indicated significant and negative path relations between knowledge and attitudes (β=− 2.271, P< 0.001), and between knowledge and practice (β=− 0.398, P< 0.001). Extended SEM analysis, which divides knowledge into K1, K2, and K3 parts, showed negative path relations between K3 and attitude (β=− 1.300, P=0.002), between attitude and practice (β=− 0.634, P< 0.001). Moreover, SEM for family members showed positive path relations between knowledge and attitude (β=1.536, P< 0.001), between attitude and practice (β=0.682, P< 0.001).Conclusion: Patients in Northern China demonstrated insufficient knowledge, negative attitude, and proactive practice, while their family members had insufficient knowledge, positive attitude, and proactive practice toward psoriasis. It is recommended to implement educational interventions addressing knowledge gaps among patients and families.Keywords: knowledge, attitude, practice, psoriasis, patients and family members, questionnaire, cross-sectional study